2013
DOI: 10.1111/iju.12098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kampo extracts on urinary stone formation: An experimental investigation

Abstract: Abbreviations & AcronymsObjective: To examine the effects of Kampo extracts on the process of urinary stone formation. Methods: A total of 14 Kampo extracts (10 mg/mL) were examined in vitro by assessing whether they could inhibit two critical steps in the early process of calcium oxalate stone formation, namely crystal aggregation and crystal adhesion to the renal tubular epithelium of Madin-Darby canine kidney cells. The inhibitory effect of the extracts on stone formation was examined by using a rat model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In previous studies, Nishihata et al. 16 reported that the Kampo extracts Takusha and Sanshishi showed obvious inhibitory effects on CaOx aggregation (64.2 and 84.5%, respectively) and on crystal adhesion to Madin-Darby canine kidney cells (54.6 and 88.2%, respectively). However, in our in vitro assays, RPA had a dose-dependent effect on formed crystals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, Nishihata et al. 16 reported that the Kampo extracts Takusha and Sanshishi showed obvious inhibitory effects on CaOx aggregation (64.2 and 84.5%, respectively) and on crystal adhesion to Madin-Darby canine kidney cells (54.6 and 88.2%, respectively). However, in our in vitro assays, RPA had a dose-dependent effect on formed crystals.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Additionally, in our experiments, RPA not only dissolved formed crystals but also inhibited crystal formation, which is analogous to the inhibitory effect of Takusha and Sanshishi on CaOx crystal formation. 16 …”
Section: Discussionmentioning
confidence: 99%
“…One of the Kampo medicine, choreito (CRT) is indicated for the symptomatic relief of the patients with following symptoms: decreased urine volume, dysuria, and cystitis 7–9 . In particular, CRT is widely prescribed for the spontaneous excretion of urinary tract stones, 10 and it has been reported that one of its actions is to inhibit the formation of oxalate calcite stones 11 . There are also several clinical reports that administration of CRT to patients with hemorrhagic cystitis improved urinary symptoms such as dysuria, pollakisuria, urinary urgency, and residual urine 12 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In particular, CRT is widely prescribed for the spontaneous excretion of urinary tract stones, 10 and it has been reported that one of its actions is to inhibit the formation of oxalate calcite stones. 11 There are also several clinical reports that administration of CRT to patients with hemorrhagic cystitis improved urinary symptoms such as dysuria, pollakisuria, urinary urgency, and residual urine. 12 The purpose of the present study is to exploratory investigate the effect of CRT on IC/BPS-like symptoms induced by tranilast.…”
mentioning
confidence: 99%
“…A . orientale also has therapeutic effects on hyperlipidaemia 6,7 , chronic prostatitis 8 , chronic obstructive pulmonary disease 9 , hepatic steatosis 10 , diabetes 11 , prophylaxis of urolithiasis 12 , anti-atherosclerotic actions 13 , cholestasis 14 , chronic kidney disease 15 and cancer 1618 .…”
Section: Introductionmentioning
confidence: 99%